Number 17 (December 1987) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1987)
(December 1987) - Morphometric and Meristic Characteristics of a Peripheral Population of Enneacanthus. By M.S. Peterson and S.T. Ross, 4 pp. Ecology of the Muscadine Darter, Percina sp. of. P. macrocephala, in the Tallapoosa River, Alabama, with Comments on Related Species. By W. Wieland and J.S. Ramsey, 7 pp. plus News Notes.
Keywords: fishes; peripheral; enneacanthus; muscadine darter; percina; p. macrocephala; tallapoosa river